The politics of external approval: explaining the IMF's evaluation of austerity programmes - Hinterleitner, Markus; Sager, Fritz; Thomann, Eva (European journal of political research, 2016)
During the European debt crisis, numerous states launched austerity programmes. The International Monetary Fund (IMF) evaluates and forecasts the likelihood of member states’ success in implementing these programmes. Although IMF evaluations influence country risk perceptions on capital markets, little is known about their reasoning. This article uses fuzzy-set qualitative comparative analysis (fsQCA) to explore on what grounds the IMF evaluated the success prospects of austerity programmes during the European debt crisis. Results reveal that IMF evaluations are heavily influenced by the programme's implementation credibility. They require a tractable policy problem, a country's institutional capacity to structure implementation, and favour expenditure reduction over revenue measures. By acting as a strict guide on the road to fiscal adjustment, the IMF indirectly influences member states’ scope of policy making through its surveillance activities. Extensive austerity programmes that need to be implemented swiftly are evaluated negatively if the country is not involved in an IMF programme.